Ultrastructure of intracytoplasmic Rickettsia-like infection of the gills of the teleost Archosargus probatocephalus (Sparidae) in northeastern Brazil - Silva,Themis Jesus (2020)
Abstract A histopathological survey was conducted to investigate the presence of microparasites in fish Archosargus probatocephalus in a river near Maceió, Brazil. Light microscope observations of fragments of gill showed the presence of small cysts containing numerous myxospores that were morphologically identified as Henneguya. Transmission electron microscopy observations further revealed several gill cells containing groups of prokaryotic cells within large cytoplasmic vacuoles. Each infected host cell displayed a single vacuole containing a variable number of Rickettsia-like cells (up to 11), some of which presented the dumbbell shape characteristic of binary fission. The Rickettsia-like cells were pleomorphic, without a nucleus and with chromatin dispersed in the cytoplasm. They had a thin electron-dense wall of Gram-negative type. The morphology of these prokaryotic was similar to those of the order Rickettsiales and was described as a Rickettsia-like organism. Histopathological evaluation showed that several vacuole membranes had a lysed appearance. Some had ruptured, thus allowing direct contact between the Rickettsia-like organism and the cytoplasm of the host cell. The rupturing of the branchial epithelium may have contributed towards reduction of the surface area of the gills, but it is not possible to say that this was the cause of the host’s death.